CORE Model in Improving Students' Mathematical Representation Ability Based on Cognitive Style - Salam, Asa Raila; Khusna, Hikmatul (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
This studynalyzes the effects of the CORE learning model on the mathematical representation abilities of junior high school students based on Field Independent (FI) and Field Dependent (FD) cognitive styles. Using a quasi-experimental methodology, this study involved 68 eighth-grade students from SMPN 169 Jakarta, divided into an experimental group using the CORE model and a control group with conventional learning. Study instruments included GEFT and mathematical representation ability tests. ANOVA analysis results indicate significant differences (F=48.655; p<0.05) between these groups, with the highest mean values in the FD experimental group (8.53), followed by the FI experimental group (7.84), FD control group (6.31), and FI control group (4.44). This study proves that the CORE learning model provides a significant effects in improving students' mathematical representation abilities, especially when combined with their cognitive styles.